Learning Implementation Utilizing Audio-Visual Media During the Covid-19 Pandemic in Children in Ekasakti Kindergarten Padang - Mutia Adila; Nurhafizah Nurhafizah (Universitas Pendidikan Indonesia Kampus Serang, 2021)
Early childhood is a child in the golden age range or the age of 0-8 years. Concerning this, learning media will help the effectiveness of the learning process, which can be used as an intermediary in stimulating all aspects of development in children. However, teachers sometimes ignore the use of media, even though using learning media, especially audio-visual media, can play an essential role in positively affecting children's learning processes. Therefore, the research aims to describe the flow technique for implementing learning using audio-visual media during the COVID-19 pandemic at Ekasakti Kindergarten. This type of research is descriptive qualitative research. The research tools were the researchers themselves, supported by observation, interviews, and documentation. The subjects of this study were teachers during the COVID-19 pandemic in teaching utilizing audio-visual media. The results uncovered that learning activities with audio-visual media during the COVID-19 pandemic had been carried out correctly and adequately for children so that delivery to children could run well and accomplish the goals to be achieved. In the activities carried out through audio-visual media, it appeared that the teachers were indeed preparing the planning, implementation, and evaluation of the learning process utilizing the audio-visual so that the delivery to children could run well and meet the goals to be achieved